-4k2(7k2 - 2k + 1)

Question

Asked 6/22/2011 10:56:19 PM

Updated 8/10/2014 5:39:41 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [8/10/2014 5:39:41 PM]

Expert answered|osborned|Points 53|

Expert answered|osborned|Points 53|

Question

Asked 6/22/2011 10:56:19 PM

Updated 8/10/2014 5:39:41 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [8/10/2014 5:39:41 PM]

Rating

3

-4k^2(7k^2 - 2k + 1) = -28k^4 + 8k^3 - 4k^2

Added 8/10/2014 5:39:40 PM

This answer has been confirmed as correct and helpful.

21 (x - 1) + x = 100 - 2 (x - 1)

Question

Not Answered

Updated 2/18/2014 3:26:07 PM

1 Answer/Comment

21 (x - 1) + x = 100 - 2 (x - 1)

21x - 21 + x = 100 - 2x + 2

22x -21 = 102 - 2x

22x + 2x = 102 + 21

24x = 123

x = 123/24

X = 41/8

21x - 21 + x = 100 - 2x + 2

22x -21 = 102 - 2x

22x + 2x = 102 + 21

24x = 123

x = 123/24

X = 41/8

Added 2/18/2014 3:26:07 PM

This answer has been confirmed as correct and helpful.

5x + 5 (x - 3) = 15
**Weegy:** x=3 (which would make it 15 + 0 = 15) **User:** x + 3 (x - 4) = 2 (x - 2) - 20
**Weegy:**
((3 / 5) * 0.6) - ((2 / 3) * 0.15) = 0.26 Thanks for asking Weegy. **User:** 10 - 5 (x - 5) = 4 (x - 1)
**User:** The sale price of a suit is three-fifths of the original price. Let p denote the original price of the suit. Express the sale price of the suit in terms of p **Weegy:** The answer is 25. (More)

Question

Expert Answered

Updated 8/10/2014 5:29:23 PM

3 Answers/Comments

5x + 5 (x - 3) = 15;

5x + 5x - 15 = 15;

10x = 15 + 15;

10x = 30;

x = 30/10;

x = 3

5x + 5x - 15 = 15;

10x = 15 + 15;

10x = 30;

x = 30/10;

x = 3

Added 8/10/2014 5:27:11 PM

This answer has been confirmed as correct and helpful.

x + 3 (x - 4) = 2 (x - 2) - 20;

x + 3x - 12 = 2x - 4 - 20;

4x - 12 = 2x - 24;

4x - 2x = -24 + 12;

2x = -12;

x = -12/2;

x = -6

x + 3x - 12 = 2x - 4 - 20;

4x - 12 = 2x - 24;

4x - 2x = -24 + 12;

2x = -12;

x = -12/2;

x = -6

Added 8/10/2014 5:28:06 PM

This answer has been confirmed as correct and helpful.

10 - 5 (x - 5) = 4 (x - 1);

10 - 5x + 25 = 4x - 4;

-5x + 35 = 4x - 4;

-5x - 4x = -4 - 35;

-9x = -39;

x = -39/-9;

x = 13/3

10 - 5x + 25 = 4x - 4;

-5x + 35 = 4x - 4;

-5x - 4x = -4 - 35;

-9x = -39;

x = -39/-9;

x = 13/3

Added 8/10/2014 5:29:23 PM

This answer has been confirmed as correct and helpful.

4 - 9x = 29 - 4x
**Weegy:**
4 - 9x = 29 - 4x;
-9x + 4x = 29 - 4;
-5x = 25;
x = 25/-5;
x = -5
**User:** 3x + 1 = 82 - 6x
**Weegy:**
3x + 1 = 82 - 6x,
3x + 6x = 82 - 1;
9x = 81,
x = 81/9, x = 9
**User:** 4/5x - 1 = 1/5x + 17 **Weegy:**
4/5x - 1 = 1/5x + 17;
4/5x - 1/5x = 17 + 1;
3/5x = 18;
x = 18/(3/5);
x = 90/3;
x = 30 **User:** 9n - 6 = 5n - 30
**Weegy:**
9n - 6 = 5n - 30;
9n - 5n = -30 + 6;
4n = -24;
n = -24/4;
n = -6
**User:** 21 (x - 1) + x = 100 - 2 (x - 1)
**Weegy:**
21 (x - 1) + x = 100 - 2 (x - 1);
21x - 21 + x = 100 - 2x + 2;
22x - 21 = 102 - 2x;
22x + 2x = 102 + 21;
24x = 123;
x = 123/24
x = 41/8 (More)

Question

Expert Answered

Updated 8/10/2014 5:38:45 PM

0 Answers/Comments

27,694,301

questions answered

There are no comments.